2012
DOI: 10.1037/a0028337
|View full text |Cite
|
Sign up to set email alerts
|

Differentiating amongst characteristics associated with problems of professional competence: Perceptions of graduate student peers.

Abstract: Diego Joint Doctoral Program in Clinical PsychologyLimited previous literature on peers infiuenced by students with problems of professional competence has descriptively focused on rates of peer identification and actions in response to identification. Prior research has suggested that students who exhibit diminished functioning due to life Stressors or psychological distress may be qualitatively different than students who lack the capacity to ever perform the duties of a competent professional psychologist. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 22 publications
1
26
0
Order By: Relevance
“…The items of interest in the current analysis were developed by the authors to target two domains: (a) student perceptions of faculty problems of professional functioning, particularly ethical misbehavior; and (b) the potential impact of perceived ethical violations on students. Students also answered a number of questions about their perception of mental health stigma within training programs; however, those items were outside the scope of the current analysis (Reddy, Docherty, January, & Meyerson, 2011) The survey was adapted from a previous study of graduate student perceptions of peers with problems of professional competence (Veilleux, January, VanderVeen, Reddy, & Klonoff, 2012a). Additional items identified in the literature as being important aspects of competence for clinical supervisors were included, with some modifications to ensure that they were broadly applicable to faculty, such as removing or altering wording specific to clinical supervision to more generally capture facultystudent interactions (Barnett, Erickson Cornish, Goodyear, & Lichtenberg, 2007;Ladany et al, 1999).…”
Section: Methodsmentioning
confidence: 99%
“…The items of interest in the current analysis were developed by the authors to target two domains: (a) student perceptions of faculty problems of professional functioning, particularly ethical misbehavior; and (b) the potential impact of perceived ethical violations on students. Students also answered a number of questions about their perception of mental health stigma within training programs; however, those items were outside the scope of the current analysis (Reddy, Docherty, January, & Meyerson, 2011) The survey was adapted from a previous study of graduate student perceptions of peers with problems of professional competence (Veilleux, January, VanderVeen, Reddy, & Klonoff, 2012a). Additional items identified in the literature as being important aspects of competence for clinical supervisors were included, with some modifications to ensure that they were broadly applicable to faculty, such as removing or altering wording specific to clinical supervision to more generally capture facultystudent interactions (Barnett, Erickson Cornish, Goodyear, & Lichtenberg, 2007;Ladany et al, 1999).…”
Section: Methodsmentioning
confidence: 99%
“…In a review of the literature, only seven published studies considered students perspectives, with two in counselor education (Gaubatz & Vera, ; Parker et al, ) and five in psychology (Mearns & Allen, ; Oliver, Bernstein, Anderson, Blashfield, & Roberts, ; Rosenberg, Getzelman, Arcinue, & Oren, ; Shen‐Miller et al, ; Veilleux, January, VanderVeen, Reddy, & Klonoff, ). Mearns and Allen () noted from survey data that 95% of students ( N = 73) acknowledged knowing a student with professional deficits, and 42% indicated that they had confronted the student of concern.…”
Section: Research Investigating Students' Perspectivesmentioning
confidence: 99%
“…Students expressed concern that trainers, who they believed were aware of the competency problems in fellow students, would not intervene. Veilleux et al () surveyed 570 individuals from 169 clinical psychology training programs to investigate students' perspectives related to peers experiencing professional competency problems. Of those surveyed, 56% indicated that they knew one or more peers with competency issues, and 54% of the students believed that faculty were aware of these students of concern.…”
Section: Research Investigating Students' Perspectivesmentioning
confidence: 99%
“…VanderVeen, Reddy, & Klonoff, 2012). When PPC are identified and informal approaches are insufficient, programs need to initiate a remediation process aimed at ensuring the trainee has the structure and support to acquire or reacquire the competencies needed to complete the training experience successfully (American Psychological Association, 2016).…”
mentioning
confidence: 99%